Effect of Environmental Laws on Protection of Ecosystem - Lesirma, Simeon (International Journal of Environmental Sciences, 2016)
Purpose: Environmental law is a body of law, which is a system of complex and interlocking statutes, common law, treaties, conventions, regulations and policies which seek to protect the natural environment which may be affected, impacted or endangered by human activities. Some environmental laws regulate the quantity and nature of impacts of human activities: for example, setting allowable levels of pollution or requiring permits for potentially harmful activities. Findings: The study also concludes that some of the above laws have been successful in environmental protection. From the study we can also conclusively argue that some of the environmental laws in place have failed to achieve their purpose. In light with the above literature review, the study concludes that most developed and developing countries have environmental laws in place. These laws include: Clean Air Act (CAA), The Clean Water Act (CWA), Drinking Water Act (SDWA), The Toxic Substances Control Act (TSCA) and The Solid Waste Disposal Act and Resource Conservation and Recovery Act (RCRA). This is a clear indicator that most governments and law making institutions are conscious about environmental protection. Policy recommendations: This study provides implications for both policy and practice. This study recommends that the government which is the institutions mandated to formulate laws in many countries should pass stringent and effective environmental laws for protecting the environment. The law enforcers and the judiciary should work hand in hand in making sure the environmental law in place is obeyed and stiff penalties levied on the offenders.